Seksisme Bahasa dan Sastra Arab - Handayani, Rizqi (Fakultas Adab dan Humaniora, UIN Syarif Hidayatullah Jakarta, Indonesia, 2010)
This research finds that there are many people use negative and discriminative character toward the woman relating with their bodies and sexuality in language and literary works. In fact, the character and imagewhich arise are based on the language and culture which the works have been produced. The idea of sexuality and the body in literary works always meet to the reality, social, politic, and cultural affair so that it often forgetthe women's experience as the author and the readers. Moreover, the rule of Arabic language tends to be discriminative, producing myth, symbol, and negative image toward the woman. Since Arabic language containing bias gender creates binary opposition, namely feminine and masculine, the literary language tends to be discriminative.The research finds that thesanctity of men masculinity in ARabic culture transforms the ideology and idea of oatriarchal which are andocentric inÂ literary works. The use of Arabic metaphorical language of gender in the style of literary writing has an effect in the emergence of stereotype, interpretation, and the dichotomy translation, which trap readers in the nuance of patriarchy and patriarkhi.